Response of the equatorial and low-latitude ionosphere over the West Pacific Ocean Sector to an X1.2 solar flare on 15 May 2013. Issue 5 (1st September 2017) - Mao, Tian; Sun, Lingfeng; Wang, Yungang; She, Chengli; Xiong, Bo; Hu, Lianhuan
Abstract: On the basis of multiple observations of ionosondes, meteor radars, magnetometers and GNSS receivers, we present the response of the equatorial and low latitude ionosphere over the West Pacific Ocean Sector to an X1.2 solar flare that peaked at 1:48 UT on 15 May 2013. The geomagnetic H component observations indicate the equatorial electrojet strength over the East Asia region is obviously enhancement during the flare. After the end time of solar flare, the ionosonde observations at Guam, an ionosonde station near the geomagnetic equatorial region, show the decrease of the peak height of ionospheric F2 layer which is related to the decrease of the eastward electric field. Simultaneous strong southern wind is observed by meteor radar over Sanya, a geomagnetic low latitude station, which probably product the westward dynamo electric field and further result in the decrease of vertical drift velocity over the geomagnetic equatorial region. In addition, GNSS total electron content (TEC) observations from six stations in the researching region show the TEC enhancement only appears nearby the geomagnetic equator region.